High-strength and high-conductivity copper alloy and preparation method thereof
By using Cu-Al pre-alloy spherical powder and CuO powder in copper alloys and hot isostatic pressure treatment, a solid-soluble Al and internal oxidized Al2O3 structure was formed, which solved the problems of complex and high cost of existing copper alloy preparation methods, and achieved high strength and high conductivity effects.
Patent Information
- Application Number
- CN202510119704.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing high-strength, high-conducting copper alloy preparation methods are complex, costly, and poor dispersion and stability of nanomaterials, which affects the performance of the material.
By mixing Cu-Al pre-alloy spherical powder with CuO powder in a specific ratio, vacuum ball milling and hot isostatic pressure treatment, an alloy structure of solid-soluble Al and internal oxidized Al2O3 is formed, thereby improving the strength and conductivity of the material.
It realizes copper alloys with high strength and high conductivity, while simplifying the process, reducing costs, and is suitable for industrial production.
Smart Images

Figure CN119876686A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper alloy and a preparation method thereof, and in particular to a high-strength and high-conductivity copper alloy and a preparation method thereof. Background Art
[0002] Copper and its alloys have excellent electrical conductivity and mechanical properties. Their excellent electrical conductivity is reflected in: pure copper has extremely high electrical conductivity, which is superior to many other materials, ensuring efficient current transmission and power conversion; low resistivity is reflected in: compared with other metals, copper has a lower resistivity, which enables it to reduce energy loss and improve energy efficiency during current transmission; good stability is reflected in: copper and copper alloys have stable electrical conductivity, are not easily affected by the external environment, and can maintain stable electrical conductivity under different environments; excellent ductility is reflected in: pure copper has excellent ductility and can extend 30-50% , which makes copper less likely to break or deform when subjected to external forces; strong plasticity is manifested in that copper has good plasticity and can be made into copper products of various shapes and sizes, such as various accessories, parts, etc., through heating and deformation; moderate strength is manifested in that pure copper has a certain strength to a certain extent. Although its strength is lower than that of other metal materials such as steel and aluminum, the strength of pure copper can remain stable at low and high temperatures, making it one of the main materials for manufacturing high-temperature corrosion-resistant equipment; good work hardening effect is manifested in that pure copper has a high work hardening index and a good strengthening effect through cold deformation, which helps to improve its mechanical properties and service life. However, copper and copper alloys also have some disadvantages: although pure copper has good electrical conductivity and corrosion resistance, and its electrical conductivity is extremely high, its strength, wear resistance, and tensile strength are low; although copper-silver alloy has high electrical conductivity, high strength, wear resistance, and high temperature resistance, Ag is a precious metal with high cost, which is not suitable for large-scale use, and the market demand is low-priced copper alloys; although copper-tin alloy has high strength and hardness, low cost, and high yield, its corrosion resistance and heat resistance are poor, which shortens its life in engineering applications and affects its stability and reliability; although copper-magnesium alloy has better performance, the easy oxidation and ablation of magnesium makes its processing technology the most complex and difficult; although copper-chromium-zirconium alloy has the best comprehensive performance, the burning of Zr element during the alloy preparation process, and the instability of the components generated by chemical reactions between Zr and elements such as Cu are key technical difficulties. Therefore, the development of a low-cost, high-strength and high-conductivity copper alloy and its preparation method is of great significance in the fields of electricity, electronics, transportation, etc.
[0003] CN117758100A discloses a high-strength and high-conductivity copper alloy material, wherein the raw materials for preparing the copper alloy material include liquid A and liquid B; the raw materials for preparing the liquid A include gadolinium oxide, copper acetate, chromium oxide, strontium oxide and aqueous sulfuric acid solution; the raw materials for preparing the liquid B include copper acetate, ethanol, methanol, hydrazine, graphene nano-microsheets and black phosphorus; the mass ratio of the liquid A to the liquid B is 1:2.8-3.2. Since the raw materials for preparing the material contain gadolinium oxide, graphene nano-microsheets and black phosphorus at the same time, the material has both high strength and high conductivity. However, the copper alloy material involves the mixing and preparation process of multiple raw materials, including the preparation of liquid A and liquid B and the subsequent processing steps, which requires complex equipment and operation techniques, increasing the difficulty and cost of preparation; at the same time, nanomaterials such as graphene nano-microsheets and black phosphorus may have poor dispersibility and stability in liquids, which may lead to uneven distribution of raw materials during the preparation process, thereby affecting the performance of the final copper alloy material.
[0004] CN115044800A discloses a novel high-strength and high-conductivity copper alloy, which contains Co, Ti or Fe, Ti compound particles and a Cu matrix; and the Cu matrix of the copper alloy contains a large number of dislocations, Co, Ti or Fe, Ti compound particles pinned at the intersection of dislocation lines; the preparation method of the copper alloy is to introduce a certain amount of Co and Ti or Fe and Ti elements into the Cu matrix, and exist in the Cu lattice in the form of solid solution atoms, then use three-dimensional cold deformation to distort the Cu lattice to contain a large number of dislocation lines, and finally use an aging heat treatment process to make Co and Ti or Fe and Ti solid solution atoms migrate rapidly along the dislocation lines, and form Co, Ti or Fe, Ti compound particles at the intersection of the dislocation lines. However, since the preparation process involves multiple complex physical and chemical processes, such as solution, cold deformation and aging heat treatment, these processes may affect the stability of the material's performance, especially during cold deformation and aging heat treatment, slight changes in parameters may lead to significant fluctuations in material performance; at the same time, the preparation method of the copper alloy mentions that Co, Ti or Fe, Ti compound particles are pinned at the intersection of dislocation lines. This structure can enhance the strength of the material. However, this structure may also cause the interaction between dislocations and compound particles to become complicated when the material is subjected to external forces, thereby affecting the plasticity and toughness of the material. Therefore, while the copper alloy and its preparation method have potential advantages, there are also some areas that need to be improved and optimized.
[0005] CN113502408A discloses a high-conductivity copper alloy containing tellurium and nickel and a preparation method thereof. The invention adopts pure copper as a matrix, adds nickel, iron and tellurium to form a quaternary alloy, uses graphite flakes as a covering agent, and phosphor copper alloy as a deoxidizer. The components are added in sequence according to their melting points for melting, and the high-conductivity copper alloy is prepared through a melting and casting process. Among them, nickel and iron elements, nickel and iron are solid-dissolved to expand the plasticity of iron in the alloy, and at the same time improve the strength of pure copper, thereby overcoming the disadvantage that the copper-iron alloy of traditional process has high strength but low plasticity. Tellurium element improves the cutting performance of the alloy and the high conductivity of pure copper, thereby obtaining a high-performance copper alloy which can maintain the mechanical properties of the copper alloy and has high conductivity, high strength and good cutting performance. However, the preparation of this alloy requires precise melting and casting processes, including adding materials, melting, deoxidation and casting in sequence according to the melting point. These steps may increase the complexity and technical difficulty of the preparation and require higher production skills and equipment requirements. At the same time, the element tellurium has certain toxicity. If the pollutant is not handled properly, it will cause long-term environmental pollution and affect human health.
[0006] In summary, it is urgent to find a high-strength and high-conductivity copper alloy and its preparation method with good electrical conductivity and mechanical properties, simple process, green and environmental protection, low cost, and suitable for industrial production. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects in the prior art and provide a high-strength and high-conductivity copper alloy with good electrical conductivity and mechanical properties.
[0008] The technical problem further to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a preparation method of high-strength and high-conductivity copper alloy with simple process, green environmental protection, low cost and suitable for industrial production.
[0009] The technical solution adopted by the present invention to solve the technical problem is as follows: a high-strength and high-conductivity copper alloy is prepared by mixing Cu-Al pre-alloyed spherical powder and CuO powder in a mass ratio of 100 to 400:1 (preferably 150 to 350:1, more preferably 200 to 300:1); the mass fraction of Al in the Cu-Al pre-alloyed spherical powder is 0.1 to 0.5% (preferably 0.1 to 0.3%), and the rest is copper; the Al element in the solid solution state in the high-strength and high-conductivity copper alloy is partially oxidized to Al by CuO; 2 O 3 The Cu element in the Cu-Al pre-alloyed spherical powder is the main component of the high-strength and high-conductivity copper alloy, providing the matrix material of the alloy; the Al element in the Cu-Al pre-alloyed spherical powder exists in the form of Al solid solution, which is the subsequent partial internal oxidation to form the dispersion strengthening phase Al 2 O 3CuO powder is an important precursor of Al; CuO powder is the oxygen source in the internal oxidation reaction, which is the oxygen source for the internal oxidation of Al element to Al 2 O 3 Provides the necessary oxygen element.
[0010] Appropriate CuO dosage allows some Al elements to be internally oxidized to form Al 2 O 3 The alloy structure with two forms of Al coexisting has the following advantages: 1) Unoxidized Al exists in the copper matrix in the form of solid solution, which increases the resistance to dislocation movement and improves the strength of the alloy, i.e., the solid solution strengthening effect. 2 O 3 The particles are dispersed in the copper matrix as the second phase. These fine particles can effectively hinder the movement of dislocations, grain boundary sliding and limit the grain size, thereby further improving the strength of the alloy, namely the dispersion strengthening effect; 2) It has a more optimized microstructure. The synergistic effect of dispersion strengthening and solid solution strengthening makes the phase interface of the alloy more tightly bonded, the defect density is lower, and the stress distribution is more uniform, so that the alloy can maintain high strength while maintaining good toughness; 3) Although Al 2 O 3 It is an insulator, and its presence in large quantities will significantly reduce the conductivity of the alloy. However, Al existing in the Cu matrix in the form of solid solution together with the Cu matrix constitutes a more complex conductive network. This network structure increases the paths and channels for electron transmission, making the transmission of electrons in the alloy smoother, thereby maintaining the conductivity of the alloy at a high level; 4) The solid-solution Al element helps to reduce the deformation resistance of the alloy, and in subsequent processing such as hot extrusion, it plays a role in improving the processing performance of the alloy and improving the processing efficiency.
[0011] Preferably, the average particle size of the Cu-Al pre-alloyed spherical powder is 60 to 100 μm. During the ball milling process, the Cu-Al pre-alloyed spherical powder with an average particle size of 60 to 100 μm will neither cause uneven powder mixing due to excessively large particles nor increase the time and energy consumption of ball milling due to excessively small particles; at the same time, under this average particle size, it is helpful to optimize the kinetic process of chemical reactions such as internal oxidation, making the reaction more sufficient and uniform, and has good fluidity and compressibility during the operation process, which is convenient for ball milling powder mixing and subsequent pressing, sintering and other process steps, thereby improving the quality and performance of the product.
[0012] Preferably, the average particle size of the CuO powder is 2-8 nm. CuO powder with an average particle size of nanometers can be evenly attached to the Cu-Al pre-alloyed spherical powder by ball milling. If the particle size of the CuO powder is too large, it will be difficult to attach to the main powder.
[0013] Preferably, the Cu-Al pre-alloyed spherical powder is an atomized Cu-Al pre-alloyed spherical powder. More preferably, the Cu-Al pre-alloyed spherical powder is a water-atomized Cu-Al pre-alloyed spherical powder. The Cu-Al pre-alloyed spherical powder formed by water atomization has a small and uniform grain size. The reduction in grain size helps to improve the strength and toughness of the material, and also helps to improve the conductivity of the material. Water as an atomization medium is not only cheap but also high in purity, which makes water atomization powder making extremely economical and further reduces production costs.
[0014] The technical solution adopted by the present invention to further solve the technical problem is as follows: A method for preparing a high-strength and high-conductivity copper alloy comprises the following steps: (1) Powder mixing: first, mix the Cu-Al pre-alloyed spherical powder with the CuO powder, and then vacuum dry it to obtain an alloy mixed powder; (2) isostatic pressing: first, the alloy mixed powder obtained in step (1) is injected into a mold, firstly subjected to cold isostatic pressing, and then the obtained green body is subjected to hot isostatic pressing to obtain a copper alloy preform; (3) Hot extrusion: The copper alloy preform obtained in step (2) is preheated and then hot extruded to obtain a high-strength and high-conductivity copper alloy.
[0015] Preferably, in step (1), the mass ratio of the Cu—Al pre-alloyed spherical powder to the CuO powder is 100 to 400:1 (more preferably 150 to 350:1, and even more preferably 200 to 300:1).
[0016] Preferably, in step (1), the Cu-Al pre-alloyed spherical powder and the CuO powder are vacuum dried before mixing. Vacuum drying before mixing can prevent the powder from getting wet and moisture in the drying process from causing the alloy powder to be oxidized.
[0017] Preferably, in step (1), the powder mixing includes vacuum ball milling or vacuum V-type mixing. More preferably, the vacuum ball mill is a vacuum planetary ball mill. Powder mixing can achieve uniform mixing of Cu-Al powder and CuO, thereby improving the structural uniformity of the composite material. This improvement in uniformity helps to reduce stress concentration and improve the strength and toughness of the material; the interface between Cu-Al powder and CuO will be fully mixed and refined during the powder mixing, especially ball milling, to form a large number of interfaces. These interfaces can improve the internal bonding force of the material through physical and chemical effects, thereby enhancing the mechanical properties of the material and playing an interface strengthening role.
[0018] Preferably, the ball-to-material ratio of the vacuum ball mill is 1 to 4:1, the ball mill speed is 200 to 400 r / min, and the vacuum is evacuated to -0.1 MPa for 1 to 20 hours (more preferably 2 to 15 hours). The purpose of vacuum milling is to prevent the heated air in the powder mixing process from causing the aluminum in the Cu-Al pre-alloyed spherical powder to be oxidized. This side reaction will consume the aluminum that should have participated in the internal oxidation reaction, resulting in unsatisfactory results of the subsequent internal oxidation reaction. The effect of this ordinary oxidation is completely different from internal oxidation. If the ball-to-material ratio and the ball mill speed are too small or the time is too short, the effect of the ball milling powder mixing will deteriorate, and CuO will be difficult to evenly distribute in the powder, resulting in internal oxidation Al formed by CuO oxidation. 2 O 3 The dispersed phase is difficult to appear evenly, resulting in abnormal performance; the appropriate ball-to-material ratio helps to improve the powder mixing effect, allowing the nano-CuO powder to be adsorbed on the Cu-Al pre-alloyed spherical powder, and the appropriate ball milling speed and time can avoid lattice distortion and defects that may occur during the ball milling process.
[0019] Preferably, stainless steel balls with a diameter of 2 to 4 mm are used for vacuum ball milling.
[0020] Preferably, the vacuum ball milling includes vacuum dry milling and vacuum wet milling.
[0021] Preferably, before the vacuum wet grinding, anhydrous ethanol is first added into the ball mill to cover the balls and materials.
[0022] Preferably, the stirring speed of the vacuum V-type mixing is 10-40 r / min, and the vacuum is evacuated to -0.1 MPa for 1-5 hours. The V-type mixing mainly relies on the relative movement and collision between powder particles to achieve mixing.
[0023] Preferably, in step (1), the temperature of vacuum drying before and after the powder mixing is 50-80°C, the vacuum is evacuated to -0.1MPa, and the time is 8-14h. The vacuum drying after vacuum dry grinding is to prevent some water in the ball tank from entering the alloy mixed powder, while the vacuum drying after vacuum wet grinding is to volatilize and recover ethanol and separate the grinding balls from the alloy mixed powder.
[0024] Preferably, in step (1), when the mixed powder is vacuum ball-milled, sieving is performed after vacuum drying. In actual operation, the ground stainless steel balls and the alloy mixed powder are vacuum dried together, and then the balls and materials are separated by sieving.
[0025] Preferably, the screening comprises air bag type air flow screening.
[0026] Preferably, the air flow rate of the air bag type airflow screening is 800-1200m3 / h.
[0027] Preferably, the mesh size of the sieve is 18-240, which is slightly larger than the powder particle size and much smaller than the planetary ball milling ball, so as to facilitate screening out suitable alloy mixed powder. More preferably, the material of the sieve is 316L.
[0028] Preferably, in step (2), the working pressure of the cold isostatic pressing is 150-250 MPa (more preferably 170-230 MPa), the temperature is room temperature, and the time is 5-15 min (more preferably 6-12 min). Cold isostatic pressing compresses the gaps between the powder particles and forms the powder material by applying equal pressure in all directions to the alloy mixed powder at room temperature, thereby increasing the density of the powder and providing a green body for further hot isostatic pressing process.
[0029] Preferably, in step (2), the working pressure of the hot isostatic pressing treatment is 50-150 MPa, the temperature is 800-1000°C, and the time is 2-4 hours. Under the combined effect of high temperature and high pressure in the hot isostatic pressing treatment, the powder body is further densified. At the same time, during the hot isostatic pressing process, the oxygen generated by the decomposition of CuO oxidizes part of the Al in the Cu-Al matrix to generate Al 2 O 3 Forming a dispersed strengthening phase, Al 2 O 3 The particles are finely dispersed in the matrix, which plays a role in strengthening the matrix and realizing the density molding of the powder material at the same time, forming a material with high strength and high density; and the dispersed strengthening phase can hinder the expansion of cracks, thereby improving the crack resistance of the material. It can also enhance the bonding force of the material interface, and together with the solid solution strengthening of the unoxidized solid solution form Al, it hinders the dislocation movement and grain boundary sliding of the material when it is stressed, improves the strength and hardness of the material, and further improves the mechanical properties and hardness. In addition, the high temperature and high pressure environment of hot isostatic pressing helps to eliminate the residual stress generated in the material preparation process and improve the mechanical properties and stability of the material.
[0030] Preferably, in step (3), the copper alloy preform is preheated to 800-1000°C at a heating rate of 2-8°C / min and then kept warm for 20-60 minutes. 2 O 3 The dispersed phase copper alloy material has higher plasticity at high temperature. When the temperature of the copper alloy preform reaches 900℃, the thermal motion of atoms inside it intensifies and the bonding force between atoms weakens, thereby reducing the deformation resistance of the material, making the extrusion process smoother and more extrudable.
[0031] Preferably, while the copper alloy preform is preheated, the extrusion barrel is preheated to 350-450°C (more preferably 370-430°C), and the orifice plate mold is preheated to 400-500°C (more preferably 420-480°C). As molds for hot extrusion molding of high-strength and high-conductivity copper alloys, the extrusion barrel and the orifice plate mold can better reduce the deformation resistance at the temperature, and the copper alloy preform is also easier to extrude. At the same time, the requirements for mold material performance and price due to the need to withstand excessively high temperatures can be reduced. The size and shape of the holes on the orifice plate mold are different, which determines the different thickness and shape of the extruded high-strength and high-conductivity copper alloy.
[0032] Preferably, after the preheating and before the hot extrusion, the orifice plate die is installed on the bottom of the extrusion cylinder, and the copper alloy preform is loaded into the extrusion cylinder.
[0033] Preferably, in step (3), the extrusion speed of the hot extrusion is 5 to 15 mm / s (more preferably 7 to 13 mm / s), and the extrusion ratio is 20 to 40. During the hot extrusion process, the copper alloy preform that has been subjected to hot isostatic pressing is further processed into a desired shape, and the grains are refined during the extrusion process. At the same time, the material undergoes plastic deformation under high pressure, further eliminating internal pores and defects, improving the density of the material, and enhancing the mechanical properties and processing properties of the material.
[0034] The inventive idea of the method of the present invention is: by adding CuO powder as a heterogeneous additive to the copper alloy Cu-Al powder, and ball milling to achieve uniform mixing of the Cu-Al powder and CuO, the Cu-Al powder and CuO are fully mixed and refined, thereby improving the uniformity of the structure of the composite material; at the same time, hot isostatic pressing is combined to decompose the oxygen of CuO to internally oxidize part of the Al element to produce Al 2 O 3 It can increase the effective nucleation sites and form solid solution strengthening with the remaining solid solution Al, thereby hindering the dislocation movement and grain boundary sliding of the material when it is stressed, and jointly improving the uniformity of the material's organization, reducing impurities and defects. In addition, the solid solution Al and the Cu matrix together form a more complex conductive network. This network structure increases the path and channel for electron transmission, making the transmission of electrons in the alloy smoother and forming a special conductive channel. The above factors work together to significantly improve the mechanical properties and conductivity of the composite material.
[0035] The beneficial effects of the method of the present invention are as follows: (1) The high-strength and high-conductivity copper alloy of the present invention has good electrical conductivity and mechanical properties, with an ultimate tensile strength of up to 513.37 MPa, an elongation of up to 26.3%, a conductivity of up to 92.1%, and a hardness of up to 84.6 HRB. It can better solve the technical bottleneck of being hindered in the application of electricity, circuits, and transportation due to its limited conductivity and strength, and has good promotion and application value; (2) The method of the present invention has simple process, is green and environmentally friendly, has low cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 are SEM images of the alloy mixed powders obtained after mixing the powders in step (1) of embodiments 1 to 4 of the method of the present invention (corresponding to (a), (b), (c), and (d) in sequence); Figure 2 are SEM images of the green bodies obtained after cold isostatic pressing in step (2) of embodiments 1 to 4 of the method of the present invention (corresponding to (a), (b), (c), and (d) respectively); Figure 3 are SEM images of the copper alloy preforms obtained after hot isostatic pressing in step (2) of embodiments 1 to 4 of the method of the present invention (corresponding to (a), (b), (c), and (d) in sequence); Figure 4 are SEM images of the high-strength and high-conductivity copper alloys obtained in steps (3) of embodiments 1 to 4 of the method of the present invention (corresponding to (a), (b), (c), and (d) in sequence); Figure 5 is a SEM image (a) of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 1 of the method of the present invention and its corresponding EDS element distribution map of Cu, Al and O; Figure 6 is a SEM image (a) of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 2 of the method of the present invention and its corresponding EDS element distribution map of Cu, Al and O; Figure 7 is a SEM image (a) of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 3 of the method of the present invention and its corresponding EDS element distribution map of Cu, Al and O; Figure 8 is a SEM image (a) of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 4 of the method of the present invention and its corresponding EDS element distribution map of Cu, Al and O; Fig. 9 1 is a SEM image (a) of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 2 of the method of the present invention and its corresponding EPMA image of Cu, Al and O. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments and drawings.
[0038] The water-atomized Cu-Al pre-alloyed spherical powder used in the embodiments of the present invention and the comparative examples has an Al mass fraction of 0.2%, a Cu mass fraction of 99.8%, an average particle size of 80 μm, and is purchased from Zhuzhou Smelting Group Co., Ltd.; the CuO powder used in the embodiments of the present invention and the comparative examples has an average particle size of 5 nm and is purchased from Suzhou Youzirconium Nanomaterials Co., Ltd.; the raw materials or chemical reagents used in the embodiments of the present invention and the comparative examples, unless otherwise specified, are obtained through conventional commercial channels.
[0039] A high-strength and high-conductivity copper alloy embodiment 1 to 4 The high-strength and high-conductivity copper alloy is prepared by mixing water-atomized Cu-Al pre-alloyed spherical powder and CuO powder in a mass ratio of 243.9:1; the Al element in the solid solution state in the high-strength and high-conductivity copper alloy is partially oxidized into Al by CuO. 2 O 3 exists in the Cu matrix in the form of.
[0040] A high-strength and high-conductivity copper alloy embodiment 5 The high-strength and high-conductivity copper alloy is prepared by mixing water-atomized Cu-Al pre-alloyed spherical powder and CuO powder in a mass ratio of 299.4:1; the Al element in the solid solution state in the high-strength and high-conductivity copper alloy is partially oxidized to Al by CuO. 2 O 3 exists in the Cu matrix in the form of.
[0041] A high-strength and high-conductivity copper alloy embodiment 6 The high-strength and high-conductivity copper alloy is prepared by mixing water-atomized Cu-Al pre-alloyed spherical powder and CuO powder in a mass ratio of 200:1; the Al element in the solid solution state in the high-strength and high-conductivity copper alloy is partially oxidized into Al by CuO. 2 O 3 exists in the Cu matrix in the form of.
[0042] A method for preparing a high-strength and high-conductivity copper alloy Example 1 (1) Powder mixing: First, 5 kg of water-atomized Cu-Al pre-alloyed spherical powder and 20.5 g of CuO powder were placed in a planetary ball mill, and a stainless steel ball with a diameter of 3 mm was used. The ball-to-material ratio was 2:1. The speed of the ball mill was 300 r / min, and the vacuum was evacuated to -0.1 MPa. The vacuum planetary ball mill was used for dry grinding of the mixed powder for 2 h. Then, the vacuum was evacuated to -0.1 MPa at 60 °C, and vacuum dried for 10 h. Then, the mixed powder was placed in an air bag airflow sieving machine and the air flow rate was 1000 m 3 / h, 316L sieve with a mesh size of 120, air bag type airflow screening is performed to obtain alloy mixed powder; The water-atomized Cu-Al pre-alloyed spherical powder and the CuO powder are first vacuumed to -0.1 MPa at 60° C. and vacuum dried for 10 hours before mixing. (2) Isostatic pressing: first, the alloy mixed powder obtained in step (1) is injected into a mold, and firstly, cold isostatic pressing is performed at a working pressure of 200 MPa and room temperature for 8 minutes, and then the obtained green body is hot isostatically pressed at a working pressure of 100 MPa and 900° C. for 3 hours to obtain a copper alloy preform; (3) Hot extrusion: The copper alloy preform obtained in step (2) is preheated to 900°C at a heating rate of 5°C / min and kept warm for 30 min. At the same time, the extrusion barrel is preheated to 400°C and the orifice plate mold is preheated to 450°C. The orifice plate mold is then installed at the bottom of the extrusion barrel. The copper alloy preform is loaded into the extrusion barrel and hot extrusion is performed at an extrusion speed of 10 mm / s and an extrusion ratio of 30 to obtain a high-strength and high-conductivity copper alloy.
[0043] A method for preparing a high-strength and high-conductivity copper alloy Example 2 The difference between the embodiment of the present invention and the method embodiment 1 is that: in step (1), the vacuum planetary ball milling wet grinding and mixing are carried out for 2 hours, and before the vacuum planetary ball milling wet grinding and mixing, anhydrous ethanol is first added to the planetary ball milling tank and the balls and materials are covered. The rest is the same as the method embodiment 1.
[0044] A method for preparing a high-strength and high-conductivity copper alloy Example 3 The difference between the embodiment of the present invention and the method embodiment 1 is that in step (1), the vacuum planetary ball mill is used to dry grind the powder mixture for 10 hours. The rest is the same as the method embodiment 1.
[0045] A method for preparing a high-strength and high-conductivity copper alloy Example 4 The difference between the embodiment of the present invention and the method embodiment 1 is that in step (1), 5 kg of Cu-Al pre-alloyed spherical powder and 20.5 g of CuO powder are first placed in a vacuum V-type mixer, and the mixture is vacuumed to -0.1 MPa at a stirring speed of 30 r / min for 4 hours, and then vacuumed to -0.1 MPa at 60° C. and vacuum dried for 10 hours to obtain an alloy mixed powder. The rest is the same as the method embodiment 1.
[0046] like Figure 1 As shown, in the steps (1) of Examples 1 to 3 of the method of the present invention, after the powders are mixed by ball milling dry milling for 2 hours, ball milling wet milling for 2 hours, and ball milling dry milling for 10 hours, respectively, the obtained mixed powders are severely broken, the powder particle size is fine, and the powder has a large number of irregular shapes, and some of them are in the form of fragments, among which the powders mixed by ball milling wet milling for 2 hours have the finest particle size; while after the V-shaped mixing for 4 hours in step (1) of Example 4 of the method of the present invention, the obtained mixed powder has a relatively high degree of sphericity and reduces the agglomeration phenomenon during the mixing process.
[0047] like Figure 2 As shown, in step (2) of embodiments 1 to 4 of the method of the present invention, the mixed powder obtained in step (1) is respectively subjected to cold isostatic pressing to be fully compacted in the mold, and the resulting embryo body has a tight structure, cracks and defects, and a uniform grain distribution, which is ready for the subsequent hot isostatic pressing operation.
[0048] like Figure 3 As shown, in steps (2) of embodiments 1 to 4 of the method of the present invention, the blanks produced by cold isostatic pressing are respectively subjected to hot isostatic pressing to make them more fully compacted in the mold. Compared with the cold isostatic pressed blanks, the cracks and defects are fully improved, and the grains are all finer. The copper alloy preforms obtained by steps (2) of embodiments 1 to 3 of the method of the present invention have relatively fewer overall defects and higher density, while the copper alloy preforms obtained by step (2) of embodiment 4 of the method of the present invention have slightly more cracks appearing at the grain boundaries and slightly more hole defects. In addition, the copper alloy preforms obtained by step (2) of embodiment 2 of the method of the present invention have the smallest grain size. At the same time, in the copper alloy preforms obtained by steps (2) of embodiments 1 to 4 of the method of the present invention, it can be observed that in addition to the defects, there are also some gray-black spots, which are presumed to be Al formed by oxidation during hot isostatic pressing. 2 O 3 .
[0049] like Figure 4 As shown, the high-strength and high-conductivity copper alloys obtained in steps (3) of embodiments 1 to 4 of the method of the present invention have a more densified surface than the copper alloy preform obtained in step (2); the high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 2 of the method of the present invention still has the highest density, and the high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 4 of the method of the present invention has the lowest density; the high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 2 of the method of the present invention has the smallest grain size, and the high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 4 of the method of the present invention has the largest grain size.
[0050] In order to determine whether the gray-black spots in the SEM of the high-strength and high-conductivity copper alloy obtained in step (3) of embodiments 1 to 4 of the present invention are Al2O3 formed by internal oxidation during hot isostatic pressing, 2 O 3 , use EDS element distribution map to observe the distribution of each element, and circle the position of the gray-black spots on the SEM image corresponding to the EDS element distribution map of Al and O. If Al and O elements are co-segregated and can completely overlap, it is Al formed by hot isostatic pressing internal oxidation. 2 O 3 .
[0051] like Figures 5 to 8As shown, the high-strength and high-conductivity copper alloy obtained in step (3) of embodiments 1 to 4 of the method of the present invention has obvious co-segregation of Al and O elements, which can be overlapped with the gray-black spots in the SEM image. Among them, the gray-black spots of the high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 2 of the method of the present invention are more numerous and most diffuse, that is, Al 2 O 3 Better dispersed in the matrix.
[0052] In order to further detect whether the gray-black spots in the SEM of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 2 of the present invention are Al 2 O 3 , and further analysis was performed using EMPA electron probe.
[0053] like Fig. 9 As shown in the SEM image of the high-strength and high-conductivity copper alloy obtained in step (3) of Example 2 of the method of the present invention, the gray-black spots in the Al and O element distribution diagram indicate that the intensity of the Al element is relatively high, further confirming that the gray-black spots in the SEM are Al 2 O 3 .
[0054] A method for preparing a high-strength and high-conductivity copper alloy Example 5 (1) Powder mixing: first, 5 kg of water-atomized Cu-Al pre-alloyed spherical powder and 16.7 g of CuO powder are placed in a planetary ball mill; the rest is the same as step (1) of method embodiment 2; (2) Isostatic pressing: first, the alloy mixed powder obtained in step (1) is injected into a mold, and firstly, cold isostatic pressing is performed at a working pressure of 200 MPa and room temperature for 8 minutes, and then the obtained green body is hot isostatically pressed at a working pressure of 150 MPa and 1000° C. for 4 hours to obtain a copper alloy preform; (3) Same as step (3) of Example 2.
[0055] The copper alloy preform obtained in step (2) of Example 5 of the method of the present invention is examined by scanning electron microscopy. It can be seen that the obtained preform has a lower level of pores and cracks at the grain boundaries, has a better density, the grain morphology becomes more irregular and larger grains appear, and the gray-black spots are distributed more evenly, but the distribution density is slightly lower than that of the copper alloy preform obtained in step (2) of Example 2 of the method.
[0056] The copper alloy preform obtained in step (2) of Example 5 of the method of the present invention is tested by EDS, and it can be seen that part of Al and O elements are co-segregated at the gray-black spots to generate Al 2 O 3 The number is reduced, but the distribution is more even.
[0057] A method for preparing a high-strength and high-conductivity copper alloy Example 6 (1) Powder mixing: first, place 5 kg of water-atomized Cu-Al pre-alloyed spherical powder and 25 g of CuO powder in a planetary ball mill; the rest is the same as step (1) of method embodiment 2; (2) Same as step (2) in Example 2; (3) Hot extrusion: The copper alloy preform obtained in step (2) is preheated to 1000°C at a heating rate of 5°C / min and kept warm for 60 min. At the same time, the extrusion barrel is preheated to 400°C and the orifice plate mold is preheated to 450°C. The orifice plate mold is then installed at the bottom of the extrusion barrel. The copper alloy preform is loaded into the extrusion barrel and hot extrusion is performed at an extrusion speed of 10 mm / s and an extrusion ratio of 40 to obtain a high-strength and high-conductivity copper alloy.
[0058] The copper alloy preform obtained in step (2) of embodiment 6 of the method of the present invention is examined by scanning electron microscopy. It can be seen that the grain size of the obtained preform is relatively small, the grain morphology is relatively regular, and finer grain clusters appear in some areas. There are fewer pores and cracks at the grain boundaries, and gray-black spots are distributed more at the grain boundaries. Aggregation also occurs in the grain cluster area, but the distribution density is slightly lower than that of the copper alloy preform obtained in step (3) of embodiment 2 of the method.
[0059] The copper alloy preform obtained in step (2) of Example 6 of the method of the present invention is detected by EDS, and it can be seen that more Al and O elements are co-segregated at the gray-black spots to generate Al 2 O 3 There are many, but some areas are Al 2 O 3 Particles cluster.
[0060] The high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 6 of the method of the present invention is detected by scanning electron microscopy. It can be seen that the grain size of the high-strength and high-conductivity copper alloy obtained is still generally smaller than that of the copper alloy preform, the grain morphology is more regular, the finer grain clusters and grain boundaries have fewer pores and cracks, the gray-black spots are redistributed in the copper matrix, the distribution is more uniform, the density is improved, and the distribution density is equivalent to the high-strength and high-conductivity copper alloy obtained in step (3) of embodiment 2 of the method.
[0061] The high-strength and high-conductivity copper alloy obtained in step (3) of Example 6 of the method of the present invention is tested by EDS. It can be seen that the clustering phenomenon of Al and O co-segregation area in the obtained high-strength and high-conductivity copper alloy is fully improved. 2 O 3 Redistributed in the copper matrix, the distribution is more uniform.
[0062] A method for preparing a copper alloy Comparative Example 1 The difference between the comparative example of the present invention and method example 2 is that in step (1), no CuO powder is added; in step (3), a copper alloy is obtained. The rest is the same as method example 2.
[0063] Scanning electron microscopy shows that the copper alloy embryo containing solid-solution Al element obtained by cold isostatic pressing in step (2) of comparative example 1 of the present invention and the copper alloy preform obtained by hot isostatic pressing have improved cracks and defects compared with cold isostatic pressing, but the grain size has no obvious change. This is because without the presence of CuO, the solid-solution Al element cannot be internally oxidized to Al 2 O 3 , there is no Al 2 O 3 Limit the growth of grains.
[0064] The copper alloy obtained in step (3) of comparative example 1 of the present invention is detected by scanning electron microscopy. It can be seen that the grain morphology is relatively regular and evenly distributed, the grain size tends to decrease, but the grains are still large in size, and there are many cracks and defects on the surface.
[0065] A method for preparing a copper alloy Comparative Example 2 The difference between the comparative example of the present invention and method example 2 is that: in step (1), 5 kg of Cu-Al pre-alloyed spherical powder and 45 g of CuO powder are first placed in a planetary ball mill; in step (3), a copper alloy is obtained. The rest is the same as method example 2.
[0066] The copper alloy obtained in step (3) of comparative example 2 of the present invention is detected by scanning electron microscopy. It can be seen that the grain size of the copper alloy obtained is small, and more grain boundaries are generated, but more cracks and holes appear at the grain boundaries. At the same time, the gray-black spots are less distributed and show a large area aggregation phenomenon. This is because the addition of too much CuO reduces the ratio of Cu-Al pre-alloyed spherical powder to CuO powder, the CuO particles are unevenly distributed, and the Al generated during the internal oxidation process is 2 O 3 Agglomeration occurs. Although the copper alloy presents fine grains, excessive grain refinement produces too many grain boundaries, which become channels for crack propagation and have poor density.
[0067] The copper alloy obtained in step (3) of comparative example 2 of the present invention was tested by EDS, and it was found that Al and O elements were severely segregated at the gray-black spots, making the Al 2 O 3 The dispersed phase is not dispersed enough.
[0068] A method for preparing a copper alloy Comparative Example 3 The difference between the comparative example of the present invention and method example 2 is that: in step (1), 5 mm stainless steel balls and 10 mm stainless steel balls are used in a mass ratio of 6:4, and the ball-to-material ratio is 2:1; in step (3), a copper alloy is obtained. The rest is the same as method example 2.
[0069] The alloy mixed powder obtained in step (1) of comparative example 3 of the present invention is detected by scanning electron microscopy. It can be seen that the Cu-Al pre-alloyed spherical powder is crushed violently and presents a cohesive fragment. The size of the fragment is larger than that of the alloy mixed powder obtained in step (1) of embodiment 2 of the method of the present invention. This is because during the ball milling process, the contact area between the larger sphere diameter and the powder particles is smaller, and the collision frequency is also reduced, so the particle size of the alloy powder cannot be effectively refined. At the same time, since the size of the 5 and 10 mm stainless steel balls is larger, a larger impact force will be generated during the ball milling process, resulting in an increase in the cold welding phenomenon between the powder particles, causing adhesion between the particles.
[0070] The copper alloy obtained in step (3) of comparative example 3 of the present invention was detected by SEM, and the obtained copper alloy had deep surface cracks and partial pores, and the density was slightly poor. The larger copper alloy powder particle size resulted in more casting defects in the copper alloy.
[0071] A method for preparing a copper alloy Comparative Example 4 The difference between the comparative example of the present invention and method embodiment 2 is that in step (1), the ratio of balls to materials is 5:1; in step (3), a copper alloy is obtained. The rest is the same as method embodiment 2.
[0072] The alloy mixed powder obtained in step (1) of comparative example 4 of the present invention was detected by scanning electron microscopy. It can be seen that the Cu-Al pre-alloyed spherical powder was crushed violently and was finely broken. Finely broken powder and large agglomerated powder can also be observed. This is because the mass of the grinding balls is relatively high, and the collision frequency and force between the grinding balls and the powder increase, which may cause the powder particles to be over-grinded and produce too much fine powder; and the over-fine powder particles have a high specific surface area and surface energy, which are easy to attract each other and agglomerate; and CuO is not evenly distributed on the Cu-Al pre-alloyed spherical powder.
[0073] The copper alloy obtained in step (3) of comparative example 4 of the present invention was tested by EDS and found that no trace dispersed Al 2 O 3 The fine precipitated phase has micropores and defects, and the oxygen content is distributed more. The Cu-Al pre-alloyed spherical powder is oxidized during the process. This is because the above-mentioned fine powder and agglomerates are not easy to be removed during the casting process, resulting in micropores and defects inside the casting. At the same time, the high ball-to-material ratio may lead to increased friction between the grinding ball and the powder during the grinding process, generating more heat, causing oxidation of the powder surface and introducing impurities.
[0074] A method for preparing a copper alloy Comparative Example 5 The difference between the comparative example of the present invention and method embodiment 2 is that: in step (2), the temperature of hot isostatic pressing treatment is 1100° C.; in step (3), a copper alloy is obtained. The rest is the same as method embodiment 2.
[0075] The copper alloy obtained in step (3) of comparative example 5 of the present invention was tested by SEM, and it was found that the surface of the copper alloy had many cracks and partial pores, the grains were relatively large, and there were large and less distributed gray-black spots. This is because at higher temperatures, the atomic diffusion rate in the copper matrix is accelerated, resulting in a significant growth of the grains and a reduction in the number of grain boundaries. At the same time, greater thermal stress is generated inside the material, resulting in the formation or expansion of pores and cracks, thereby reducing the density of the copper alloy material.
[0076] The copper alloy obtained in step (3) of comparative example 5 of the present invention is tested by EDS, and it is found that Al and O elements are segregated at the gray-black spots, and the larger Al 2 O 3 particles. This is because higher temperatures will cause Al 2 O 3 The particles aggregate, grow or coarsen, that is, larger and less distributed gray-black spots appear, thus reducing the effect of diffusion strengthening.
[0077] In order to evaluate the ultimate tensile strength, elongation, conductivity and hardness of the high-strength and high-conductivity copper alloys obtained in Examples 1 to 6 of the method of the present invention and the copper alloys obtained in Comparative Examples 1 to 5, the ultimate tensile strength (MPa) and elongation (%) of the above copper alloys were tested according to the national standard GB / T34505-2017; the conductivity (%) of the above copper alloys was tested according to the national standard GB / T 32791-2016; the hardness (HRB) of the above copper alloys was tested according to the national standard GB / T2059-2017; the results are shown in Table 1.
[0078]
[0079] As shown in Table 1, in Examples 1 to 4 of the method of the present invention, planetary ball milling and V-type mixing are used, wherein the planetary ball milling adopts different dry and wet ball milling processes. In the dry ball milling process of Example 1 of the method of the present invention, the powder particles are refined by the impact and shearing action of the ball milling medium; at the same time, in the dry ball milling process, due to the stirring and dispersing action, the Cu-Al pre-alloyed spherical powder and the CuO powder can be mixed together more evenly, and this uniform mixing is conducive to the formation of more and evenly distributed Al in the hot isostatic pressing internal oxidation process. 2 O 3 Dispersed phase, due to more Al 2 O 3It is dispersed in the Cu matrix, can pin dislocations and inhibit grain growth, thereby refining grains and improving the overall strength of the material, and has only a small number of defects and cracks, reducing stress concentration under external force conditions, and having good ultimate tensile strength and hardness; relative to Example 1 of the method of the present invention, due to the presence of anhydrous ethanol, a liquid medium, in the wet grinding process of Example 2 of the method of the present invention, it plays a lubricating and cooling role, and the density is higher. This is because during the wet grinding process, the powder particles are assisted by the liquid medium, and the impact and shearing action of the ball milling medium make the refinement faster and more uniform, and the gaps between small particles are smaller, which is easier to fill by diffusion and plastic flow. Therefore, the refined powder particles are easier to densify during the hot isostatic pressing process; at the same time, during the ball milling wet grinding process, due to the stirring and dispersing effect of the liquid medium, the uniformity of the mixing of the Cu-Al pre-alloyed spherical powder and the CuO powder is better than that of the ball milling dry grinding, and more and more uniformly distributed Al is formed during the hot isostatic pressing internal oxidation process. 2 O 3 Dispersed phase, better ultimate tensile strength and hardness; at the same time, the material with high density has fewer pores and defects, fewer obstacles encountered by electrons in the transmission process, and better conductivity; since the impact and shearing effect of the ball milling medium on the powder particles in Example 1 of the method of the present invention is not as good as that of wet ball milling, the plastic deformation degree and dislocation accumulation of the powder particles in the process of dry ball milling are relatively low, and the degree of work hardening is low, which makes the powder particles relatively easier to absorb energy through slip and deformation in the subsequent hot isostatic pressing process, showing a higher elongation; Compared with Example 1 of the method of the present invention, as the ball milling time increases, the powder particles are gradually refined under the impact and shearing action of the ball milling balls, and the mixing between Cu-Al powder and CuO powder is more uniform, and Al 2 O 3 The generation and distribution of the powder are also more dispersed, therefore, both fine grain strengthening and dispersion strengthening can be achieved simultaneously, with better effect; compared with Example 1 of the method of the present invention, Example 4 of the method of the present invention adopts V-shaped mixing, and the powders are evenly mixed by rotation and flipping, thereby better maintaining the original spherical shape of the powders. The spherical powders reduce the slight imbalance between strength and toughness caused by powder refinement to a certain extent, so that the copper alloy has a certain toughness while maintaining high strength; at the same time, the spherical powders have good fluidity, which is beneficial to subsequent processing, therefore, the elongation of Example 4 of the method of the present invention is better.
[0080] As shown in Table 1, in Example 5 of the method of the present invention, the ratio of Cu-Al powder to CuO is increased to 299.4:1, and the blank is subjected to hot isostatic pressing for 4 hours at a working pressure of 150 MPa and 1000°C to obtain a copper alloy preform. At this time, the added CuO can only generate an appropriate amount of Al 2 O 3The high temperature and pressure and long holding time of hot isostatic pressing increase the activity of CuO, making it easier to oxidize with Al, increasing Al 2 O 3 The amount of CuO generated can be reduced, thereby improving the low addition amount of CuO. Therefore, it has a sufficient inhibitory effect on the growth of grains and can effectively pin the grain boundaries, which can weaken the growth trend of grains during the subsequent hot extrusion process, thereby also having better mechanical properties and hardness. The unconsumed solid solution Al and Cu matrix together form more complex conductive networks, which better increase the paths and channels for electron transmission, thus having high conductivity.
[0081] As shown in Table 1, in Example 6 of the method of the present invention, the ratio of Cu-Al powder to CuO is reduced to 200:1, and the green body is hot isostatically pressed to obtain a preform in the same manner as in Example 2. At this time, CuO can react more fully with the Al element in the matrix to generate a uniformly distributed and sufficient amount of Al 2 O 3 , better pinning the grain boundaries to limit the growth of grains and enhance the grain refinement effect, while some areas show excessive refinement, causing grain clusters and some cracks, making some Al 2 O 3 The particles are also concentrated in this area. Subsequently, the copper alloy preform is preheated to 1000°C at a heating rate of 5°C / min and kept warm for 60 minutes. At the same time, the extrusion barrel is preheated to 400°C, and the orifice plate mold is preheated to 450°C. The orifice plate mold is then installed at the bottom of the extrusion barrel, and the copper alloy preform is loaded into the extrusion barrel. At an extrusion speed of 10mm / s and an extrusion ratio of 40, hot extrusion is performed to obtain a high-strength and high-conductivity copper alloy. Higher hot extrusion preheating temperature, holding time and high extrusion ratio make the distribution of grains more uniform, which helps to reduce the number of grain clusters, reduce the generation of microcracks, improve the density and microstructure of the alloy, and also make Al 2 O 3 The particles are redistributed in the copper matrix, which better hinders dislocation movement and grain boundary sliding and prevents further crack expansion. Therefore, it also has higher mechanical properties and hardness.
[0082] As shown in Table 1, since no CuO powder is added to Comparative Example 1 of the present invention, the grain size in the copper alloy is large, which makes the strength of the copper alloy worse, indicating that the density, processability and conductivity of the sample cast by the pre-alloyed powder obtained by using pure metal powder are poor, and the mechanical properties are also poor; since excessive CuO is added to Comparative Example 2 of the present invention, the Al element can be completely consumed and there is still a surplus, resulting in serious segregation of Al and O elements at the gray-black spots, and the Al generated during the internal oxidation process is 2 O 3Agglomeration occurs, and small grains are formed. However, due to excessive grain refinement, too many grain boundaries are generated, and the grain boundaries become channels for crack expansion, which has poor density. At the same time, there is no complex conductive network composed of solid solution Al and Cu matrix, which reduces the path and channel of electron transmission. Therefore, the mechanical properties and conductivity are reduced. Comparative Example 3 of the present invention uses larger stainless steel balls for ball milling with the same ball-to-material ratio, and presents a fragment with adhesion. The size of the fragment is larger than that of the alloy mixed powder obtained in step (1) of Example 2 of the method of the present invention. The copper alloy obtained after hot extrusion has deeper surface cracks and partial pores, and the density is slightly poor, so The mechanical properties and electrical conductivity of the copper alloy are reduced; in comparative example 4 of the present invention, at a relatively high ball-to-material ratio of 5:1, the powder particles are over-ground, resulting in excessive fine powder and large agglomerated powder, which are not easily removed during the casting process, resulting in micropores and defects inside the casting, and the heat generated by excessive grinding causes oxidation of the powder surface, introducing impurities, thereby reducing the mechanical properties and electrical conductivity of the copper alloy; in comparative example 5 of the present invention, due to the increase in the hot isostatic pressing temperature, the resulting copper alloy has more surface cracks and partial pores, the grains are relatively large, and larger and less distributed gray-black spots appear, and Al and O elements are segregated at the gray-black spots, which is a larger Al 2 O 3 particles, low material density, reduced number of grain boundaries and Al 2 O 3 The particles aggregate, grow and coarsen, which reduces the dispersion strengthening effect and thus affects the strength and toughness of the material.
Claims
1. A high-strength and high-conductivity copper alloy, characterized in that: The high-strength and high-conductivity copper alloy is prepared by mixing Cu-Al pre-alloyed spherical powder and CuO powder in a mass ratio of 100 to 400:1; the mass fraction of Al in the Cu-Al pre-alloyed spherical powder is 0.1 to 0.5%, and the rest is copper; the Al element in the solid solution state in the high-strength and high-conductivity copper alloy is partially oxidized in CuO to Al2O3 and exists in the Cu matrix.
2. The high-strength and high-conductivity copper alloy according to claim 1, characterized in that: The average particle size of the Cu-Al pre-alloyed spherical powder is 60-100 μm; the average particle size of the CuO powder is 2-8 nm; and the Cu-Al pre-alloyed spherical powder is atomized Cu-Al pre-alloyed spherical powder.
3. A method for preparing the high-strength and high-conductivity copper alloy as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Powder mixing: first, mix the Cu-Al pre-alloyed spherical powder with the CuO powder, and then vacuum dry it to obtain an alloy mixed powder; (2) isostatic pressing: first, the alloy mixed powder obtained in step (1) is injected into a mold, firstly subjected to cold isostatic pressing, and then the obtained green body is subjected to hot isostatic pressing to obtain a copper alloy preform; (3) Hot extrusion: The copper alloy preform obtained in step (2) is preheated and then hot extruded to obtain a high-strength and high-conductivity copper alloy.
4. The method for preparing the high-strength and high-conductivity copper alloy according to claim 3, characterized in that: In step (1), the mass ratio of the Cu-Al pre-alloyed spherical powder to the CuO powder is 100 to 400:1; the Cu-Al pre-alloyed spherical powder and the CuO powder are vacuum dried before mixing; the powder mixing includes vacuum ball milling or vacuum V-type mixing; the ball-to-material ratio of the vacuum ball milling is 1 to 4:1, the speed of the ball milling is 200 to 400 r / min, the vacuum is evacuated to -0.1 MPa, and the time is 1 to 20 hours; stainless steel balls with a diameter of 2 to 4 mm are used for vacuum ball milling; the vacuum ball milling includes vacuum dry milling and vacuum wet grinding; before the vacuum wet grinding, anhydrous ethanol is first added to the ball mill and the ball and material are covered; the stirring speed of the vacuum V-type mixing is 10-40r / min, and the vacuum is evacuated to -0.1MPa for 1-5h; before and after the powder mixing, the vacuum drying temperature is 50-80°C, the vacuum is evacuated to -0.1MPa, and the time is 8-14h; when the powder mixing is vacuum ball milled, it is screened after vacuum drying; the screening includes air bag airflow screening; the air flow rate of the air bag airflow screening is 800-1200m 3 / h; the mesh size of the screening is 18 to 240 meshes.
5. The method for preparing the high-strength and high-conductivity copper alloy according to claim 3 or 4, characterized in that: In step (2), the working pressure of the cold isostatic pressing is 150-250 MPa, the temperature is room temperature, and the time is 5-15 min; the working pressure of the hot isostatic pressing treatment is 50-150 MPa, the temperature is 800-1000° C., and the time is 2-4 h.
6. The method for preparing the high-strength and high-conductivity copper alloy according to claim 3 or 4, characterized in that: In step (3), the copper alloy preform is preheated to 800-1000°C at a heating rate of 2-8°C / min, and then kept warm for 20-60 minutes; while the copper alloy preform is preheated, the extrusion barrel is preheated to 350-450°C, and the orifice plate mold is preheated to 400-500°C; after the preheating and before hot extrusion, the orifice plate mold is installed at the bottom of the extrusion barrel, and the copper alloy preform is loaded into the extrusion barrel; the extrusion speed of the hot extrusion is 5-15 mm / s, and the extrusion ratio is 20-40.
7. The method for preparing the high-strength and high-conductivity copper alloy according to claim 5, characterized in that: In step (3), the copper alloy preform is preheated to 800-1000°C at a heating rate of 2-8°C / min, and then kept warm for 20-60 minutes; while the copper alloy preform is preheated, the extrusion barrel is preheated to 350-450°C, and the orifice plate mold is preheated to 400-500°C; after the preheating and before hot extrusion, the orifice plate mold is installed at the bottom of the extrusion barrel, and the copper alloy preform is loaded into the extrusion barrel; the extrusion speed of the hot extrusion is 5-15 mm / s, and the extrusion ratio is 20-40.
Citation Information
Patent Citations
High-conductivity copper alloy containing tellurium and nickel and preparation method thereof
CN113502408A
Cited By
High-strength plastic copper alloy and preparation method thereof
CN121852756A